Association between higher ambient temperature and orthopaedic infection rates: a systematic review and meta‐analysis. Issue 9 (11th April 2019) - Vickers, Mark L.; Pelecanos, Anita; Tran, Marie; Eriksson, Lars; Assoum, Mohamad; Harris, Patrick N.; Jaiprakash, Anjali; Parkinson, Benjamin; Dulhunty, Joel; Crawford, Ross W.
Abstract : Introduction: Many infectious diseases display seasonal variation corresponding with particular conditions. In orthopaedics a growing body of evidence has identified surges in post‐operative infection rates during higher temperature periods. The aim of this research was to collate and synthesize the current literature on this topic. Methods: A systematic review and meta‐analysis was performed using five databases (PubMed, Embase, CINAHL, Web of Science and Central (Cochrane)). Study quality was assessed using the Grading of Recommendations Assessment, Development and Evaluation method. Odds ratios (ORs) were calculated from monthly infection rates and a pooled OR was generated using the DerSimonian and Lairds method. A protocol for this review was registered with the National Institute for Health Research International Prospective Register of Systematic Reviews (CRD42017081871). Results: Eighteen studies analysing over 19 000 cases of orthopaedic related infection met inclusion criteria. Data on 6620 cases and 9035 controls from 12 studies were included for meta‐analysis. The pooled OR indicated an overall increased odds of post‐operative infection for patients undergoing orthopaedic procedures during warmer periods of the year (pooled OR 1.16, 95% confidence interval 1.04–1.30). Conclusion: A small but significantly increased odds of post‐operative infection may exist for orthopaedic patients who undergo procedures during higher temperature periods. It is hypothesized that this effect is geographically dependent and confounded by meteorological factors, local cultural variables and hospital staffing cycles. Abstract : A growing body of evidence has identified surges in post‐operative infection rates following orthopaedic surgery during higher temperature periods. We conducted a meta‐analysis on this topic which included 6, 620 cases and 9, 035 controls from 12 studies. The pooled OR indicated an overall increased odds of post‐operative infection for patients undergoing orthopaedic procedures during warmer periods (pooled OR: 1.16, 95% confidence interval: 1.04–1.30).